VARIOUS FACTORS RELATED TO THE INCIDENCE OF SCABIES IN STUDENTS AT DAYAH X, ACEH BESAR DISTRICT - T.M. Rafsanjani; Dian Fitria; Masyudi Masyudi; Evi Dewi Yani; Nisrina Hanum (Universitas Bina Bangsa Getsempena, 2025)
The incidence of scabies cases at Dayah X, Aceh Besar Regency in 2021 to 2023 reached 200 cases, this was due to lack of knowledge, attitude and personal hygiene . This study aims to determine the factors related to the incidence of scabies in students at Dayah Dayah X, Aceh Besar Regency .Study This use quantitative descriptive analytical approach cross - sectional study . This study was conducted in December 2024. The population in this study were all junior high school students aged 600 students and the number of samples was 240 respondents. The sampling technique used random sampling, data were analyzed univariately and bivariately. The study showed that there was a relationship between knowledge ( p = 0.000), attitude ( p = 0.000), personal hygiene ( p = 0.038) with the incidence of scabies in students at Dayah X, Aceh Besar Regency. It is recommended that the dayah can collaborate with the health center to conduct routine visits to examine students and provide health education in the dayah environment so that scabies can be prevented.